European energy industry shocks, corporate control and firm's value (2013)
The deregulation process in the EU electricity sector triggered strategic decisions that led to industry restructuring. This paper presents preliminary evidence of the impact of this process on investors, using event studies and estimation techniques such as least squares and GARCH. Our findings suggest three stylized facts: 1) regulatory reform in Europe was certainly accompanied by a takeover wave, as predicted by Mitchell and Mulherin (1996); 2) mergers and acquisitions had a positive impact on the stock price of target firms, and a much lower and sometimes even a negative impact for the bidding firms; 3) the effect of takeover announcements on the returns of competitors of the merging firms depends on the degree of market power. In countries with high market power (like Spain) competitors significantly increase share returns upon takeover announcements, whereas in countries with lower market power (like England and Wales) returns do not change significantly.